Association of PTPN1 polymorphisms with breast cancer risk: A case‐control study in Chinese females. Issue 7 (25th February 2019) - Huang, Shuya; Liu, Liyuan; Xiang, Yujuan; Wang, Fei; Yu, Lixiang; Zhou, Fei; Cui, Shude; Tian, Fuguo; Fan, Zhimin; Geng, Cuizhi; Cao, Xuchen; Yang, Zhenlin; et al.
Abstract: Background: Breast cancer (BC) risk, development, and prognosis were closely related to obesity, diabetes mellitus, and metabolic syndrome. Protein tyrosine phosphatase, non‐receptor type 1 (PTPN1) located on chromosome 20q13, could negatively regulate insulin and leptin signaling. In this study, we determined the association of PTPN1 polymorphisms with BC risk. Methods: We analyzed the distribution of 11 selected PTPN1 single nucleotide polymorphisms in Chinese female patients with BC (n = 953) and healthy controls (n = 963) based on a multicenter case‐control study. The association of PTPN1 genotypes and haplotypes frequencies with BC risk were determined by logistic regression analysis. Analyses were further stratified by body mass index (BMI), waist‐hip rate (WHR), diabetes mellitus history, and fasting plasma glucose level. The eQTL (expression Quantitative Trait Loci) analysis for PTPN1 was conducted by GTEx database. Results: There were significant differences between BC cases and control groups in menopausal status, number of births, and BMI. Four single nucleotide polymorphisms (SNPs; rs3215684, rs3787345, rs718049, and rs718050) decreased overall BC risk, and other seven SNPs showed no significant association with BC risk. In multivariate analysis, BMI and rs3215684 DT + DD genotype were identified as independent risk factors for BC, and mutated genotypes of rs3215684 were correlated with increased PTPN1 expression. There are no haplotypes showed different frequencies between cases and controls. In the stratified analysis, rs2206656 showed a significant association with decreased BC risk in the subgroup of BMI ≤ 24 kg/m 2, while rs3215684 and rs718049 showed lower BC risk in the subgroup of WHR > 0.85. Seven SNPs showed lower BC risk in the subgroup with diabetes mellitus history and/or fasting plasma glucose level ≥ 7 mM, while rs754118 decreased BC risk in the subgroup of fasting plasma glucose level < 7 mM. Conclusion: Our findings suggest that PTPN1 SNPs associated with BC susceptibility in Chinese females, which also suggested a novel mechanism between obesity, diabetes mellitus, and BC risk. Abstract : In this study, we determined the association of PTPN1 polymorphisms with breast cancer risk in China women by multi‐center case‐control stduy. We confirmed that rs3215684 was associated with breast cancer susceptibility by affecting PTPN1 expression. Also, PTPN1 SNPs were also linked obesity and diabetes mellitus with breast cancer risk.